Effect of Anodizing Time and Annealing Temperature on Photoelectrochemical Properties of Anodized TiO2 Nanotube for Corrosion Prevention Application - Misriyani Misriyani; Abdul Wahid Wahab; Paulina Taba; Jarnuzi Gunlazuardi (Indonesian Journal of Chemistry, 2017)
A study on the influence of anodizing time, annealing temperature and photoelectrochemical properties of TiO2 nanotube (TiO2 NT) has been investigated. The crystallinity was investigated using X-Ray Diffraction and the anti-corrosion performance of stainless steel 304 (SS 304) coupled with TiO2 NT was evaluated using electrochemical techniques under ultraviolet exposure. The optimum anodizing condition occurs at a voltage of 20 V for 3 h. After anodizing, the TiO2 NT amorf was calcined at 500 °C to obtain anatase crystalline phase. For the photoelectrochemical property, the effects of pH and NaCl concentration on corrosion prevention have been examined. The result showed that the corrosion rate of stainless steel 304 coupled with TiO2 NT can be reduced up to 1.7 times compared to the uncoupled stainless steel 304 (3.05×10-6 to 1.78×10-6 mpy) under ultraviolet exposure by shifted the photopotential to the more negative value (-0.302 V to -0.354 V) at a pH of 8 and 3% NaCl concentration (-0.264 V to -0.291 V). In conclusion, the TiO2 NT films, which was prepared by anodization and followed by annealing can prevent the corrosion of stainless steel 304.